Anti-Inflammatory Potential of Phenolic Compounds Isolated From Entada africana Guill. & Perr. Used in the Republic of Benin - Codo Toafode, Nonvignon Murielle; Marquardt, Peter; Ahyi, Virgile; Fester, Karin; Spiegler, Verena; Vissiennon, Cica (Frontiers in Pharmacology, 2022)
In West African medicine, Entada africana Guill. & Perr. from the family of Fabaceae is used to treat inflammatory conditions in the management of fractures, wounds, and sprains in the northern region of the Republic of Benin. The aim of the present study was to isolate and elucidate phenolic compounds from a hydroalcoholic leaf extract from E. africana and to identify compounds with anti-inflammatory activity in vitro. Eleven compounds were purified from three fractions, which have shown strong to medium anti-inflammatory activity. The isolated compounds were characterized by HRESI-MS and NMR methods as gallic acid (1), ethyl gallate (2), 5,7-dihydroxychromen-4-one (3), 3′,4′,7-trihydroxyflavone (4), dihydrokaempferol-7-O-glucoside (5), catechin (6), quercetin-3-O-[β-apiosyl-(1‴→2″)-β-glucoside] (7), quercetin-3-O-glucoside (8), naringenin-7-O-glucoside (9), aromadendrin (10), and myricetin-3-O-glucoside (11). Nine of the major phenolic compounds were tested using TNF-α stimulated human keratinocytes (HaCaT) as skin inflammation model to identify molecules, which may explain the use of the plant leaves as an anti-inflammatory remedy by assessing the release of proinflammatory cytokines IL-8 and IL-6. The hydroacoholic leaf extract of E. africana exerted a medium inhibitory effect on the release of IL-8. 3′,4′,7-trihydroxyflavone, aromadendrin, dihydrokaempferol-7-O-glucoside and ethyl gallate demonstrated a strong to medium effect on the release of IL-6. For the release of IL-8, 3′,4′,7-trihydroxyflavone demonstrated a medium activity. This study provides for the first time a detailed screening of phenolic compounds occurring in the hydroethanolic leaf extract of E. africana. Additionally, it is shown that E. africana contains active compounds which may justify its traditional medicinal use as an anti-inflammatory remedy to treat inflammatory and pain-related skin conditions in the Republic of Benin.